ANALISIS PENDAPATAN ANGGOTA P3A USAHATANI PADI SAWAH DI DAERAH IRIGASI LOMAYA ALALE PROVINSI GORONTALO - Darmiati Dahar; Winskayati Winskayati (Agropolitan, 2018)
This study aimed to identify the characteristics and income of P3A paddy field farmers. The location of the study was purposive determined by selecting all P3A groups in Bone Bolango and Gorontalo districts. The study method used descriptive qualitative and quantitative analysis. Descriptive analysis to described the condition based on the results of the questionnaire about the identification of rice farmer characteristics of P3A members. Descriptive quantitative analysis was conducted to answer irrigation management at farmer level. The results obtained with regard to the characteristics of paddy rice farmers are members of P3A by sex predominantly male, with an average education level of high school and college, as well as being in old age and in carrying out their farming. The average income of P3A paddy farmers were Rp. 8,612,712.43 per ha or average income per hectare amount Rp. 2.344.245,84,- The results obtained from the analysis of R / C Ratio shows the profitable farming.